Mampu Menggunakan Strategi dan Metode Pembelajaran - Junita Nopitasari Butarbutar; Dorlan Naibaho (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2024)
A school or education really needs variety when the teaching and learning process or the learning process occurs in school. Why is this so necessary? So that the atmosphere of the teaching and learning process is not monotonous and boring, right? So learning strategies and methods are really needed, this is because every student has different learning potential. A small example is when a teacher teaches using a variety of learning methods, not just one learning method or strategy, it will be easier for students to understand the learning, but if a teacher only uses methods that are often used then it will automatically be difficult for students to accept and this will lead to boredom when studying, because students learn differently and the way students learn is also different. For this reason, in the teaching and learning process, strategies and learning methods should not be ignored, especially in today's increasingly sophisticated era, there are automatically so many learning strategies and methods. Learning strategies and methods are very important components for educators or are controlled by educators in the learning process so that the learning objectives to be achieved are realized.